The Impact of G6PD Deficiency on Liver Function in Children Under 15 - Saeed, Saad Mahmood; Ahmed Naji, Nazar (Tikrit Journal of Pure Science, 2024)
Glucose-6-phosphate dehydrogenase (G6PD) is involved in the first phase of the pentose phosphate pathway (PPP), entailing the reduction of nicotinamide adenine dinucleotide phosphate (NADP+) and the oxidation of glucose-6-phosphate to 6-phosphogluconolactone. A deficiency in the G6PD activity can result in numerous illnesses, including liver diseases. The first three enzymes in PPP are responsible for the oxidative phase. They make NADPH, which is needed to deal with oxidative stress, especially in people who do not have enough G6PD. The study included (90) samples from people with hemolytic anemia (Favzim) and control to determine the levels of G6PD, albumin, total protein, liver function, alanine transaminase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and bilirubin. The results showed that there was a significant decrease (P<0.05) in the serum levels of G6PD in the patients group when compared with the control group. Also, there was a significant increase (P<0.05) in the serum levels of albumin, total protein, ALP, ALT, AST and total bilirubin in patients with the G6PD deficiency when compared with the control group. In addition, this study revealed a strong positive correlation between some biochemical parameters studied, such as:  Total protein with TSB (r2 = 0.897), TSB with ALT (r2 = 0.893), AST with ALT (r2 = 0.623) and total protein with ALT (r2 = 0.804).